PENEGAKAN HUKUM TERHADAP PELAKU DAN PENYEDIA TEMPAT PERJUDIAN MESIN (GELANGGANG PERMAINAN ) DI KOTA PEKANBARU OLEH KEPOLISIAN DAERAH RIAU - Viandras Billy Gustama; Mexsasai Indra; Ferawati Ferawati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
The current criminal law in Indonesia is a criminal law that has been codified, that is, most of itand its rules have been compiled in a wetboek, called the Criminal Code, according to a particular system.Basically, criminal law does focus on regulating the problem of crimes that occur in the community. If theConstitutional Court is often referred to as The Guardian Of Constitutution, then the criminal law inrelation to crime deserves to be called The Guardian Of Security which seeks to guarantee that the peopleare not victims of crime.This research is empirical juridical research or sociological legal research. Empirical juridicalresearch is carried out by identifying the law and how the effectiveness of the law applies in society. Whilethe population and sample are parties related to the problems examined in this study, the data sources used,primary data, secondary data, and tertiary data. The technique of collecting data in this study was throughinterviews and literature review.From the results of the research the authors did can be concluded, first Law enforcement againstthe crime of gambling machines that under the guise of playing fields, with children's business permits, hasnot been optimally performed. This is evident from the fact that there are still many gambling machines thathave a game of children operating in the city of Pekanbaru. The second obstacle in law enforcement is thefirst regulation regarding gambling is still multi-interpretation. In addition to the definition of gambling, theCriminal Code does not clearly explain the prize of the game / race which can be categorized as a crime ofgambling, whether it is only money or can be replaced with other prizes.Keywords: Law Enforcement - Actors and Providers - Gambling Machines.